Online teacher training and upgrading programmes for science teachers: Issues of assessment - Rainford, Marcia (School of Education, UWI, St. Augustine, 2008)
With many science teachers from the Caribbean migrating to more developed countries in order to take up more lucrative contracts, the need to increase the training opportunities for teachers has taken on greater urgency. Online learning is considered a convenient option to address this increased demand for in-service training and upgrading of teachers. While this form of course delivery has several strengths, there are several drawbacks that are of particular significance for training and professional development of teachers. This paper highlights some of the challenges with respect to the types of assessment activities and the management of the assessment process of one university online programme involved with the professional development of teachers. It discusses some implications for graduates of this programme moving on to higher educational opportunities, with an emphasis on science education and the assessment of students enrolled in online teacher upgrading programmes
Keywords: Teacher education; Science teachers; Online courses; Student evaluation; School of Education, UWI, Mona; Jamaica